2023
DOI: 10.3390/horticulturae9020154
|View full text |Cite
|
Sign up to set email alerts
|

Widely Targeted Metabolomics Provides New Insights into the Flavonoid Metabolism in ‘Kyoho’ Grapes under a Two-Crop-a-Year Cultivation System

Abstract: The establishment and application of a two-crop-a-year cultivation system depends on the particularity of climatic conditions in subtropical regions. The different temperature, light, and water conditions throughout the growing season of summer and winter grapes are the fundamental reasons for differences in primary and secondary metabolites. We performed ultra-high-performance liquid chromatography–triple quadrupole mass spectrometry (UPLC-QQQ-MS)-based metabolomics on ‘Kyoho’ grapes under a two-crop-a-year c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Poppins', the changes across years in Mv and Dp reflected those shown in relative terms and are in line with that published by Venios et al [64]. Moreover, in all the fruits of the two cvs., the accumulation of Cy was higher under conditions of greater thermal stress, i.e., in 2022, as reported in Kyoho grape by Cheng et al [71].…”
Section: Discussionsupporting
confidence: 75%
“…Poppins', the changes across years in Mv and Dp reflected those shown in relative terms and are in line with that published by Venios et al [64]. Moreover, in all the fruits of the two cvs., the accumulation of Cy was higher under conditions of greater thermal stress, i.e., in 2022, as reported in Kyoho grape by Cheng et al [71].…”
Section: Discussionsupporting
confidence: 75%
“…The decrease in TFC in summer, autumn, and spring could be due to the natural tolerance of most plant genetic resources evaluated in this study to the extreme temperatures in these seasons, as they do not require the antioxidant activity that promotes flavonoids. Cheng et al [32] reported that only low temperatures, and not high temperatures, encourage the expression of genes fitted to produce flavonoids and, therefore, their accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted from March 2018 to January 2019 at the Guangxi Zhencheng Agriculture Co., Ltd vineyard in Nanning (23°11'48"N, 108°8'33"E). Three-year-old Shine Muscat grapevines grafted on 5BB served as experimental materials, managed under Two-Crop-A-Year (TCAY) cultivation by [31], with adjustments made for variety differences. Speci cally, short cane pruning (1-2 buds) occurred in January, with arti cial dormancy break using 50% hydrogen cyanamide (diluted 15-20 times) in January-February.…”
Section: Materials Treatmentmentioning
confidence: 99%
“…. Since the promotion and application of two-crop-a-year cultivation in Guangxi, the grape planting area has increased threefold, and the total value has risen from 260 million yuan to 2.6 billion yuan annually [31]. Two-crop-a-year cultivation effectively mitigates the impact of strong summer rainfall and heat waves, reduces losses caused by natural disasters, and allows for production cycle adjustments [30].…”
mentioning
confidence: 99%